Theodore Nouman, Vincent P. Perlo, Herbert A. Mann, Harold Rubin, and Vinson B. Conliffe, ca. 1938-39 - Munro, Melville S. (Tufts Archival Research Center, 2005)
Print is in Munro Collection, Box 078, p. 130 #19377